Pomen serumskega cistatina C za ugotavljanje okvare ledvic med kemoterapijo - Vrhovec, Levin (Medicinski razgledi, 2000)
Many cytotoxic agents used in antitumor therapies can cause a kidney damage. Therefore there is a necessity for regular kidney function monitoring before and during chemotherapy. Clearance tests have been proven to be the most accurate indicators for clinical assessment of glomerular filtration (CFR). Because of inconvenience of exogene markers (inulin, 51Cr-EDTA), endogenous creatinine clearance (ECC) is used in everyday routine work. Results obtained from ECC analysis can often be misleading due to inaccurate urine collectin. In order to avoid the inconvenient urine collecting, we are trying to find an easier and faster way of kidney function assessment. Cystatin C is a serum protein, which is a member of the cysteine proteinase inhibitors. It is produced by all nucleal cells and its production rate is independent of sex, nutrition status, acute and chronic diseases and cancer. Because it is freely filtered at the glomerulus, its serum concentration correlates with glomerularfiltration rate. The purpose of this research was to find out if theserum cystatine C concentration correlates with GFR and ECC respectively. We analysed 117 serum samples taken from 56 patients. Serum and urine creatinine concentrations were determined by method based on Jaffe reaction, ECC: was calculated from urine flow, surface area and the ratio between serum and urine creatinine concentrations. We used particle enhanced turbidimetric immunoassay (PET) for cystatin C determination. Data were statistically analysed with SimStat computer program. We used Pearson correlation method with 95% confidence interval. A good correlation coefficient (r =0.736) between the values of serum creatinine and cystatine C was established within the whole concentration interval. (Abstract truncated at 2000 characters.)
Keywords: cistatin; Cystatins; Blood; ledvice; kemoterapija; Antineoplastic agents; Adverse effects; Kidney diseases; Chemically induced; Kidney function tests; Glomerular filtration rate; Creatinine; Metabolic clearance rate; diagnostika